B cell mechanosensing regulates ER remodeling at the immune synapse - Riobó, Isidora; Yuseff, María Isabel (Frontiers in Immunology, 2024)
Engagement of the B-cell receptor with immobilized antigens triggers the formation of an immune synapse (IS), a complex cellular platform where B-cells recruit signaling molecules and reposition lysosomes to promote antigen uptake. Calcium efflux from the endoplasmic reticulum (ER) released upon BCR stimulation is necessary to promote B-cell survival and differentiation. Whether the spatial organization of the ER within the B-cell synapse can tune IS function and B-cell activation remains unaddressed. Here, we characterized ER structural changes triggered by BCR activation and evaluated how mechanical cues arising from antigen presenting surfaces affect this process. Our results show that, upon BCR activation, the ER is redistributed towards the IS independently of peripheral microtubules and accumulates around the microtubule-organization center. Our results reveal that ER remodeling during B-cell activation also depends on substrate stiffness highlighting how spatial reorganization of the ER is coupled to the context of antigen recognition and could tune B-cell responses.